LEXICAL-SEMANTIC FEATURES OF TRANSLATING IDIOMS - Rakhimova Shakhnoza Palvannozirovna (Western European Studies, 2024)
The article examines the lexical and semantic features of the translation of idioms and provides a generalized description of those available in science according to their classifications. The author reveals the content of the concept of idioms; the analysis of idiomatic expressions often used in everyday life was carried out taking into account the classification, the basis of which is the function of idioms in communication, determined by their structural and semantic characteristics
Keywords: idiom; lexical-semantic meaning; linguistic unit; concept